Análise da emissão de conversão ascendente de energia do sistema vítreo ZBLAN: Er3+ em baixa temperatura - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2006)
The upconversion process in rare earth elements (Er, Nd, Pr, Tm and Yb) doped fluoride glasses has received great attention from several researches. The main interest is its use in several technological applications as optical amplifiers and lasers. The fluoride glass (ZBLAN) is an amorphous glass and a good rare earth host material with low multiphonon relaxation, good chemical stability under diverse atmospheric conditions and low optical attenuation in the visible region of the electromagnetic spectrum. ZBLAN:Er3+ is a very well studied material of this class. However, the influence of the glass matrix in the upconversion process has not been investigated. This work presents upconversion and the luminescence spectra at T=2K and some definitions. The both spectra was obtained from 4S3/2 -> 4I15/2 transition level and its analysis show us energy reabsorption in the upconversion process. The upconversion spectrum obtained from 4I13/2 -> 4I9/2 transition with 800 nm Ti-Saphire laser show us seven of eight theoretical expected transitions. This results was compared with luminescence spectra obtained from 4I15/2 -> 4F7/2 transition with 488 nm Argon laser, wich show us the eight theoretical expected lines of 4S3/2 -> 4I15/2 transition, and confirm the correct position of this emission lines obtained from upconversion. We propose a possible path of the upconversion excitation process in this sample and an explanation (energy reabsorption process) for the disappearance of one line in upconversion emission spectra.
Keywords: upconversion; ZBLAN; érbio; upconversion; ZBLAN, érbio.; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA